The impact of climate change on the distribution of Sphyrna lewini in the tropical eastern Pacific. (September 2022) - Rodriguez-Burgos, Aura María; Briceño-Zuluaga, Francisco Javier; Ávila Jiménez, Julián Leonardo; Hearn, Alex; Peñaherrera-Palma, César; Espinoza, Eduardo; Ketchum, James; Klimley, Peter; Steiner, Todd; Arauz, Randall; Joan, Elpis
Abstract: Variability and climate change due to anthropic influence have brought about alterations to marine ecosystems, that, in turn, have affected the physiology and metabolism of ectotherm species, such as the common hammerhead shark (Sphyrna lewini) . However, the impact that climate variability may have on this species' distribution, particularly in the Eastern Tropical Pacific Marine Corridor, which is considered an area with great marine biodiversity, is unknown. The purpose of this research was to evaluate the effect of derivate impact of climate change on the oceanographic distribution of the hammerhead shark (Sphyrna lewini) in the Eastern Tropical Pacific Marine Corridor, contrasting the present and future scenarios for 2050. The methodology used was an ecological niche model based on the KUENM R package software that uses the maximum entropy algorithm (MaxEnt). The modelling was made for the year 2050 under RCP2.6 and RCP8.5 scenarios. A total of 952 models were made, out of which only one met the statistical parameters established as optimal, for future scenarios. The environmental suitability for S.lewini shows that this species would migrate to the south in the Chilean Pacific, associated with a possible warming that the equatorial zone will have and the possible cooling that the subtropical zone of the South Pacific will have by 2050, the product of changes in oceanographic dynamics. Highlights: Hammerhead sharks could migrate towards the South Pacific Ocean in response to oceanographic changes resulting from climate change Climate change affects oceanographic patterns and therefore the environmental suitability for the hammerhead shark. Ectothermic organisms such as the hammerhead shark are forced to change their distribution ranges, their physiology and metabolism due to climate change. The strategies chosen by hammerhead sharks in the face of temperature changes are adapting to new conditions or changing their movement and distribution patterns in search of the ideal temperature ranges.